2009
DOI: 10.4088/jcp.08m04150
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized, Placebo-Controlled Trial of Fluoxetine in Patients With Intermittent Explosive Disorder

Abstract: Fluoxetine treatment has a clear antiaggressive effect in impulsive aggressive individuals with IED. However, while fluoxetine's antiaggressive effects appear robust, they lead to full or partial remission of IED in less than 50% of subjects treated with fluoxetine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(68 citation statements)
references
References 0 publications
5
60
0
3
Order By: Relevance
“…In addition, an fMRI study of emotional information processing in IED-IR subjects reported enhanced amygdala activation, compared with controls, specifically, in response to exposure to angry faces. Third, treatment with fluoxetine (Coccaro et al, 2009) These data extend those of other studies, as well, by using d-FEN as the 5-HT challenge probe. Most studies have involved d,l-FEN, which contains equal quantities of its d-and l-isomers.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, an fMRI study of emotional information processing in IED-IR subjects reported enhanced amygdala activation, compared with controls, specifically, in response to exposure to angry faces. Third, treatment with fluoxetine (Coccaro et al, 2009) These data extend those of other studies, as well, by using d-FEN as the 5-HT challenge probe. Most studies have involved d,l-FEN, which contains equal quantities of its d-and l-isomers.…”
Section: Discussionsupporting
confidence: 82%
“…To understand the potential efficiency of a drug, it is important to uncover its neural mechanism of action. Previous work has shown reasonable effectiveness of another SSRI, fluoxetine, in treating IED (Coccaro et al, 2009), and hence the current findings indicate a potential neural mechanism for SSRI functioning. The results suggest that escitalopram may affect the neural mechanisms of social-emotional and social-cognitive processes.…”
Section: Escitalopram Effects In Iedsupporting
confidence: 68%
“…Moreover, males with IED tend to increase intensity ratings of angry faces after tryptophan depletion that reduces 5-HT availability (Lee et al, 2012). Conversely, fluoxetine (a selective serotonin reuptake inhibitor (SSRI) that increases 5-HT availability) was shown to reduce impulsive aggressive behavior in patients with personality disorders and comorbid IED (Coccaro et al, 2009). Two studies in other aggressive populations (Silva et al, 2010;George et al, 2011) replicated this finding.…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin has been implicated in a wide range of psychiatric disorders with antisocial and aggressive symptoms, including intermittent explosive disorder, antisocial personality disorder, and psychopathy (59)(60)(61), and these disorders are often treated with SSRIs such as citalopram (62). Our findings suggest that trait empathy measures could predict whether patients are likely to respond to SSRI treatment and imply that such treatments are less likely to succeed in psychopaths and patients with vmPFC damage, both of whom show a marked lack of empathy (63).…”
Section: Discussionmentioning
confidence: 99%